2021
DOI: 10.3390/pr9050839
|View full text |Cite
|
Sign up to set email alerts
|

Role of Yeasts in the Brewing Process: Tradition and Innovation

Abstract: Nowadays, in the beer sector, there is a wide range of products, which differ for the technologies adopted, raw materials used, and microorganisms involved in the fermentation processes. The quality of beer is directly related to the fermentation activity of yeasts that, in addition to the production of alcohol, synthesize various compounds that contribute to the definition of the compositional and organoleptic characteristics. The microbrewing phenomenon (craft revolution) and the growing demand for innovativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 143 publications
0
23
0
1
Order By: Relevance
“…Both thermal and membrane processes require an extra process step with additional costs. The resulting de-alcoholised beer can have a great loss of flavour, freshness, and body [3,24,28,54].…”
Section: Production Methods For Nablabmentioning
confidence: 99%
See 1 more Smart Citation
“…Both thermal and membrane processes require an extra process step with additional costs. The resulting de-alcoholised beer can have a great loss of flavour, freshness, and body [3,24,28,54].…”
Section: Production Methods For Nablabmentioning
confidence: 99%
“…In addition, yeast assimilates amino acids to synthesise new cells, enzymes, and proteins. Higher alcohols, carbonyl compounds, esters, sulphurcontaining compounds, and organic acids formed as fermentation by-products define the aroma profile of beer and influence its quality [24].…”
Section: Beer and Flavourmentioning
confidence: 99%
“…Iorizzo et al. (2021) indicated that wine fermented with P. kluyveri could be rich in floral and fruity aromas. This result is consistent with our research.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last 40 years, as scientific discoveries have continued to develop, amazing innovations have resulted in advances in the quality of the finished beer product. Innovation in the beer industry often involves the use of new mixtures of cereals and pseudocereals or the rediscovery of old cereals, new hop varieties or hop substitutes, new non- Saccharomyces yeast crops, fruit, vegetables, some spices, and other flavouring compounds to improve/modify the sensory characteristics of the finished product, customize a type of beer or offer a new type of different beer [ 3 , 4 , 5 ]. However, minimal progress has been made in considering raw ingredients, without malting, in the brewing process [ 6 ].…”
Section: Introductionmentioning
confidence: 99%